SENAM ANTIKORUPSI: INTERNALISASI KARAKTER ANTIKORUPSI BERLANDASKAN NILAI-NILAI RELIGIUS ANAK USIA DINI DI MASA PANDEMI COVID-19 - Desfa Yusmaliana; Suyadi Suyadi; Muhamad Tohir; Putri Sanggar Kusuma (Universitas Muhammadiyah Ponorogo, 2022)
Efforts to prevent corruption are carried out in various lines, including early childhood education scope. PAUD/TK Griya Bermain Pangkalpinang is an Islamic educational institution that instills academic values and Islamic values in which there is also an emphasis on integrity values. PAUD/TK Griya Bermain Pangkalpinang has caught that corruption prevention measures from an early age during the covid pandemic can be carried out by internalizing the importance of integrity in Islamic education by training and stimulating students through anti-corruption exercises. This research aims to develop and instill the values of integrity in early childhood students through anti-corruption gymnastics activities during the Covid 19 pandemic. This study used a qualitative approach in field research in PAUD/TK Griya Bermain Pangkalpinang. Techniques for data collecting included observation, interviews, and documents. The data were analyzed in three ways: descriptively, interpretively, and in comparison. In collaboration with parents and the University of Muhammadiyah Bangka Belitung's research team, the teacher taught students anti-corruption gymnastics and monitored students' integrity and anti-corruption habit. During the Covid-19 pandemic, it has the potential to be one of the programs through anti-corruption exercise habituation exercises that children and their parents can practice at home.